Audience Study as Catalyst in Sustainable Nollywood Yoruba Film Industry - Adejoke Adetoun Ademuyiwa; Eunice Uwadinma-Idemudia (Yoruba Studies Review)
Nollywood is the representation of the socio-cultural apparatus of Nigeria in the world cinema. Tis paper evaluates generally, film audience’s perspective in Nollywood films, and in particular non-native actors in native films. Most often, stakeholders in the film industry do not access, or are flagrantly ignorant of viewer’s feedback on the state of their production in all media of communication. Some determine this with the profit margins. Tis paper therefore evaluates the audience’s perception of non-native actors in Nollywood Yoruba native films. The area of concentration is on the quality of audience reception on native films by non-native actors. Cluster sample method is the tool of research for this paper, in which questionnaire samples were distributed among film viewers in the Yoruba speaking area in Nigeria. This is done in order to determine the performance ratings of non-Yoruba native actor’s skill of character interpretation in cultured films. Theoretical framework is anchored on Bandura’s Social Learning theory, which concentrates on impact of artistic models on the audience’s psyche. Findings reveal that audience ratings of non-native actors in Yoruba cultured films is poor, compared with their characterization in non-native setting, and this is due to wrong casting by directors who cast them against all odds in order to improve their profit margin. Findings also reveal the importance of audience study as a necessity in pre-production considerations of film shooting.